A characterization of the algebra of holomorphic functions on a simply connected domain - Derming Wang; Saleem Watson (International Journal of Mathematics and Mathematical Sciences)
Let A be a singly-generated ℱ-algebra. It is shown that A isomorphic to H(Ω) where Ω is a simply connected domain in ℂ if and only if A has no topological divisors of zero. It follows from this that there are exactly three ℱ-algebras (up to isomorphism) which are singly generated and have no topological divisors of zero.